Brochs and the Roman occupation of lowland Scotland - Macinnes, Lesley (Proceedings of the Society of Antiquaries of Scotland, 1985)
Challenges the view of lowland brochs as 'imported' by N Scottish mercenaries and destroyed in the Roman advance. Seen in their local context they appear as a natural development and an architectural expression of wealth in a complex Roman-native interrelationship.